Diligence – The Factor of Learning - Gumuliauskienė, Aušrinė (Acta Paedagogica Vilnensia, 1997)
Learning diligence is a very important factor that is greatly significant for efficient studies and self-education in general. Diligence is as important as intellectual abilities. The development of diligence depends very much upon the formation of motives. Industry as a personal quality is best revealed under the influence of standards required at school and home. Diligence becomes a permanent feature when it is included in the system of material and spiritual values. Educational activity no longer occupies first place of things valued among younger teenagers. An interest in education as well as diligence has decreased. Teachers are most likely to stimulate this quality in their pupils by using different pedagogical means, while at the same time trying to eliminate negative factors. Diligence in education is closely related to the sensibility of motivation.